2014
DOI: 10.1210/jc.2013-2834
|View full text |Cite
|
Sign up to set email alerts
|

Cinacalcet Monotherapy in Neonatal Severe Hyperparathyroidism: A Case Study and Review

Abstract: We describe the first use of cinacalcet as monotherapy for severe hypercalcemia in a newborn with NSHPT. The rapid and durable response to cinacalcet suggests that a trial of calcimimetic therapy should be considered early in the course of NSHPT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 28 publications
6
54
0
Order By: Relevance
“…Cinacalcet was effective in one NSHPT and all four NHPT patients. All four NHPT patients had a heterozygous R185Q mutation and as in FHH patients a rapid fall in PTH preceding the decrease in serum calcium was observed after cinacalcet (15,16). One patient showed a significant but temporary drop of ionized serum calcium by 0.4 mmol/l 12 h after a single dose of 20 mg/m 2 cinacalcet (15) and (Table 3).…”
Section: Casr As a Drug Target For Allosteric Modulatorsmentioning
confidence: 96%
See 2 more Smart Citations
“…Cinacalcet was effective in one NSHPT and all four NHPT patients. All four NHPT patients had a heterozygous R185Q mutation and as in FHH patients a rapid fall in PTH preceding the decrease in serum calcium was observed after cinacalcet (15,16). One patient showed a significant but temporary drop of ionized serum calcium by 0.4 mmol/l 12 h after a single dose of 20 mg/m 2 cinacalcet (15) and (Table 3).…”
Section: Casr As a Drug Target For Allosteric Modulatorsmentioning
confidence: 96%
“…There are, however, exceptions from this rule. Homozygous CASR mutations leading to only a mild overall impairment of extracellular calcium sensing may cause a FHH-like phenotype (8,12,13,14), whereas heterozygous CASR mutations causing more pronounced functional impairment can lead to neonatal hyperparathyroidism (NHPT) (15,16,17). Recently it has been found that inactivating mutations in the CASR associated G protein alpha 11 (GNA11) and in the adaptor-related protein complex 2 sigma 1 subunit (AP2S1) can also cause familial hypocalciuric hypercalcemia (FHH types 2 and 3) (18,19,20).…”
Section: Mutations Causing Loss Of Casr Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcimimetics increases the sensitivity of CASR; calcium binds to extracellular domain while calcimimetics bind to seven transmembrane domains increasing receptor sensitivity (8). Calcimimetics are reported to be effective in heterozygous mutation causing neonatal hyperparathyroidism (NH-PT); 4 reported cases did not require parathyroidectomy (9,10). Homozygous mutations causing NSHPT are mostly nonresponsive to cinacalcet as mutation affecting the seven transmembrane domains region.…”
Section: Discussionmentioning
confidence: 99%
“…cinacalcet which are reported to be effective in heterozygous cases. Children not responding to medical treatment require an early parathyroidectomy (3,4). In this report, we present a case of a Saudi female baby born to consanguineous parents with neonatal severe hyperparathyroidism presenting in the first month of life; DNA analysis revealed a novel homozygous mutation in the CASR gene.…”
Section: Introductionmentioning
confidence: 94%